The Impact of Service Quality on Customer Loyalty Through Customer Satisfaction of PT Multicom Persada International Jakarta - Indra Sani; Tin Agustina Karnawati; Widi Dewi Ruspitasari (Dinasti International Journal of Management Science, 2024)
In today's competitive business environment, firms are continuously seeking for methods to acquire a competitive advantage and assure long-term success by using proven techniques, such as concentrating on establishing client loyalty. Companies that develop great customer loyalty can not only boost client retention but also generate growth and profitability. The purpose of this investigation was to investigate and examine 1) the impact of service quality on customer satisfaction, 2) the impacts of customer satisfaction on customer loyalty, 3) the impact of service quality on customer loyalty, and 4) the effect of service quality on loyalty through customer satisfaction. This study employed a descriptive research design using quantitative methodologies. The study includes 80 respondents chosen at random from clients of PT Multicom Persada Internasional Jakarta and other cities in Indonesia. As a consequence, with a score of 0.293, customer satisfaction was determined to have a positive influence on customer loyalty. Furthermore, with a score of 0.690, service quality was found to have a positive influence on customer satisfaction. Service quality has a positive impact on customer loyalty of 0.261, and service quality influences customer loyalty through customer satisfaction, yielding a value of 0.203